Synthesis and Characterization of Niobium and Tungsten Substituted VOPO4 - Roy, Subrata Chandra; Yeasmin, Lilufer; Rahman, Mahmudur (Journal of Bangladesh Academy of Sciences, 2019)
Tungsten and Niobium substituted αII-VOPO4 structure type solid solution (V1–x-yWxNby) OPO4 where x = 0.07 and y ≤ 0.05 was synthesized by solution combustion technique followed by heating in air at 700˚C for 3 days. Further incorporation of niobium (y > 0.05) leads to a mixture of αII-VOPO4 structure type solid solution and two very weak reflections of another unknown phase. The synthesized product was characterized by X-ray powder diffraction, SEM/EDX, FTIR, and magnetic property analysis. Journal of Bangladesh Academy of Sciences, Vol. 43, No. 1, 31-37, 2019